Spectrum of Two-Magnon non-Heisenberg Ferromagnetic Model of Arbitrary Spin with Impurity - Tashpulatov, S.M. (Журнал математической физики, анализа, геометрии, 2013)
We consider a two-magnon system in the isotropic non-Heisenberg ferromagnetic model of an arbitrary spin s on a n-dimensional lattice Zⁿ. We establish that the essential spectrum of the system consists of the union of at most four intervals. We obtain lower and upper estimates for the number of three-particle bound states, i.e., for the number of points of discrete spectrum of the system. Рассмотрена двухмагнонная система в изотропной негейзенберговской ферромагнитной модели с произвольным значением спина s в n-мерной решетке Zⁿ. Установлено, что существенный спектр системы состоит из объединения не более чем четырех отрезков. Получены нижняя и верхняя оценки для количества точек дискретного спектра системы, т.е. для числа трехчастичных связанных состояний системы в n -мерной решетке Zⁿ.